2021
DOI: 10.3389/fpain.2021.744264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Stress, Sleep, and Oral Health in University Students

Abstract: Background: The COVID-19 pandemic, a disease caused by Sars-CoV-2, has become a worldwide stressor, especially as it represents a new viral infection, which spreads quickly and easily, without prior knowledge about vaccination, and absence, to this moment, of a medication that is totally effective against the disease.Objective: The aim of this observational study was to provide a general evaluation, through a questionnaire applied to students in the health field of the Federal University of Rio de Janeiro, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
5
0
2
Order By: Relevance
“…UU., Turquía, Nepal y Dinamarca. Los factores de riesgo asociados con las medidas de angustia incluyeron el género femenino, el grupo de edad más joven (≤40 años), la presencia de enfermedades crónicas/psiquiátricas, el desempleo, la condición de estudiante y la exposición frecuente a las redes sociales/noticias sobre COVID-19 (Cerqueira & Batista, 2021).…”
Section: Factores Estresantesunclassified
“…UU., Turquía, Nepal y Dinamarca. Los factores de riesgo asociados con las medidas de angustia incluyeron el género femenino, el grupo de edad más joven (≤40 años), la presencia de enfermedades crónicas/psiquiátricas, el desempleo, la condición de estudiante y la exposición frecuente a las redes sociales/noticias sobre COVID-19 (Cerqueira & Batista, 2021).…”
Section: Factores Estresantesunclassified
“…During the COVID-19 pandemic, several studies investigated the correlation of psychosomatic symptoms with the presence of episodes of teeth clenching. In a population of 370 college students, 30.5% (n = 113) reported being “very stressed” during the pandemic, with low or very low sleep quality (44.3% (n = 164)), and 113 students reported clenching their teeth during the day, associated with headache [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the COVID-19 pandemic on subjective sleep quality, prolonged sleep latency, and worsened sleep quality were evaluated using the Pittsburgh Sleep Quality Index (PSQI), and insomnia symptoms, especially sleep initiation problems, were evaluated using the Insomnia Severity Index (ISI) [ 7 , 12 ] were reported. Another study reported that 18% of university students responded in the affirmative to the item “began to have insomnia” [ 13 ].…”
Section: Introductionmentioning
confidence: 99%